1995
DOI: 10.1086/187836
|View full text |Cite
|
Sign up to set email alerts
|

Unified description of accretion flows around black holes

Abstract: We provide a uni ed description of thermal equilibria of black hole accretion disks, including the newly-discovered advection-dominated solutions. We classify the solutions on the basis of optical depth and importance of advection cooling. We demonstrate that only four physically distinct topological types of equilibria exist. Two of the types correspond to optically thin and optically thick equilibria, while the other two types are distinguished by whether advection is negligible or dominant. A stable Shakura… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
214
1
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 194 publications
(232 citation statements)
references
References 10 publications
13
214
1
4
Order By: Relevance
“…Chen et al 1995), we found that there are usually three branches of solutions at a given radius: (1) a cold solution, optically thick and geometrically thin, (2) an intermediate solution, and (3) an optically thin and geometrically thicker hot solution. Only the cold and hot solutions are both thermally and viscously stable.…”
Section: Discussionmentioning
confidence: 89%
“…Chen et al 1995), we found that there are usually three branches of solutions at a given radius: (1) a cold solution, optically thick and geometrically thin, (2) an intermediate solution, and (3) an optically thin and geometrically thicker hot solution. Only the cold and hot solutions are both thermally and viscously stable.…”
Section: Discussionmentioning
confidence: 89%
“…The discovery of ADAF solutions (Narayan & Yi 1994, 1995a, 1995bAbramowicz et al 1995;Chen et al 1995;Yuan & Narayan 2014) gave rise to the application of ADAF models in various black hole systems. These systems include the supermassive black hole in the Galactic center, Sagittarius A, low-luminosity AGNs, and black hole XRBs (e.g., Narayan et al 1998;Lasota 1999;Quataert 2001;Ho 2008;Narayan & McClintock 2008;Abramowicz & Fragile 2013).…”
Section: Adaf Disks and The Induction Equationmentioning
confidence: 99%
“…Comparisons of the α-disk model with observations of X-ray binaries and AGN are presented in [39] and [59] [60], respectively. Modern accretion flow models are discussed in [61].…”
Section: Accretion Disksmentioning
confidence: 99%